Pressure dependence of the dissociation of acetic, benzoic, mandelic and succinic acids at 298.15 K - Kumar, Anil (Thermochimica Acta, 2005)
Dissociation constants for acetic, benzoic, mandelic and succinic acids have been measured at 298.15 K as a function of pressure up to 138.8 MPa. The spectrophotometric technique using Bromocresol Green as the optical indicator was employed up to ionic strength of 0.03 mol kg(-1) in aqueous solution. Thermodynamic dissociation constants were calculated with the Davies activity coefficient equation. The pressure dependences of the ionization constants for the weak acids can be described by the equation of Lown, Thirsk and Wynne-Jones, application of which leads to accurate partial molal volume change on ionization, Delta(V) over bar (o) and compressibility change, Delta(K) over bar (o) at 0.1 MPa. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Acetic acid; benzoic acid; dissociation constants; high pressure; mandelic acid; succinic acid

Synthesis, characterization, X-ray structure and DNA photocleavage by cis-dichloro bis(diimine) Co(III) complexes - Ghosh, Smita; Barve, A. C.; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G.; Datar, P. A.; Sonawane, U. B.; Joshi, Rohini R. (Journal of Inorganic Biochemistry, 2006)
Keywords: Acetic acid; acrylic acid; oxidative conversion of propane; rare earth-doped Mo-V-Sb catalysts

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Entrainer for batch distillation of acetic acid -water system - Gadekar, S. V.; Naik, R. V.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2009)
Acetic acid-water system (AW) poses a challenge in reactive distillation, acetic acid purity and loss of acetic acid in aqueous solutions. Feasible separation of AW has been studied using entrainers but acetic acid loss in lean phase cannot be avoided. This study presents feasible region to operate column with toluene and benzene as entrainer for AW. Liquid-liquid equilibrium data and nature of tie line for ethyl acetate are given priority.
Keywords: Acetic acid; Batch distillation; Benzene; Entrainer; Toluene

Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Synthesis of ethyl acetate by esterification of acetic acid with ethanol over a heteropolyacid on montmorillonite K10 - Gurav, Hanumant; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2010)
In present work, liquid phase esterification of acetic acid with ethanol over dodecatungestophosphoric acid (DTPA) supported on K10 mommorillonite was systematically studied and optimization of process parameters was carried out The 20% m/m urpAtK tO was found to be the optimum catalyst with 90% acetic acid conversion and 100% ethyl acetate selectivity The study was also explored to see the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of acetic acid with other alcohols like methanol, iso-propanol and sr-butanol. The 20% m/m DTPA/K10 has shown increased activity with the increase in carbon number, at the same alcohol reflux The results are novel
Keywords: Acetic acid; Ethanol; ethyl acetate; Heteropolyacid; montmorillonite K10

Pseudo-homogeneous kinetic model for esterification of acetic acid with propanol isomers over dodecatungstophosphoric acid supported on montmorillonite k10 - Gurav, Hanumant R.; Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Journal of Physical Organic Chemistry, 2014)
Esterification of acetic acid with propanol isomers such as isopropanol and naEuropropanol was carried out over dodecatungstophosphoric acid (DTPA), dodecamolybdophosphoric acid ammonium salt hydrate, and sodium tungstate hydrated purified supported on montmorillonite K10, which were characterized by powder XaEuroray diffraction, BrunaueraEuro'EmmettaEuro'Teller, and temperature programmed ammonia desorption. A pseudoaEurohomogeneous (PaEuroH) kinetic model was established for esterification of acetic acid with propanol isomers over DTPA supported on montmorillonite K10. Effects of various parameters such as reaction time, speed of agitation, particle size, temperature, percent catalyst loading, molar ratio and mixture of propanol isomer were investigated in detail. The 20% (w/w) DTPA/K10 was found to be an optimum solid catalyst with 82% naEuropropanol and 53% isopropanol conversion with 100% selectivity toward propyl acetate. The 20% (w/w) DTPA/K10 catalyst was found to be reusable for three cycles. The reaction follows secondaEuroorder kinetics with activation energies of 25.53aEuro?kJaEuro?mol(a?'1) and 28.15aEuro?kJaEuro?mol(a?'1) for isopropanol and naEuropropanol, respectively. PseudoaEurohomogeneous kinetic model fitted with R-2 value of trend line 0.999. This implies that esterification reaction is kinetically controlled owing to high activation energy. Copyright a (c) 2013 John Wiley & Sons, Ltd.
Keywords: Acetic acid; dodecatungstophosphoric acid; Esterification; kinetic model; montmorillonite K10

Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics

Effect of furfural, acetic acid and 5-hydroxymethylfurfural on yeast growth and xylitol fermentation using Pichia stipitis NCIM 3497 - Bhavana, B. K.; Mudliar, Sandeep N.; Bokade, V. V.; Debnath, S. (Biomass Conversion and Biorefinery, 2024)
The valorization of C5 sugars (xylose) from hemicellulose of agro-industrial residues to xylitol, as one of the multi-products biorefinery approach, mandates the pretreatment of biomass which releases fermentable sugars along with the generation of biological inhibitors affecting xylitol fermentation. This study was therefore evaluated to understand the inhibitory kinetics of furfural, 5-hydroxymethylfurfural and acetic acid on xylitol fermentation. Xylitol fermentation was established using Pichia stipitis NCIM 3497 with xylose as a pure substrate optimized for xylitol yield and productivity of 0.48 g/g of xylose and 0.13 g/L/h, respectively. The functional relationship of yeast specific growth rate and limiting substrate (xylose) was expressed by Monod-type kinetics. The inhibition kinetics results indicated that the effect of inhibitors on xylitol fermentation was furfural > acetic acid > HMF. Furfural (500 mg/L) and acetic acid (1000 mg/L) reduced xylitol yield by 59% and 44%, respectively, with least reduction of 9.89% exhibited by HMF. The synergistic effect of 500 mg/L furfural, 500 mg/L HMF and 1000 mg/L acetic acid showed the highest reduction in xylitol yield of 67.6% as compared to the control. Kinetic studies predicted that the maximum concentration of furfural, HMF and acetic acid which inhibited P. stipitis growth was 884 mg/L, 3258 mg/L and 2922 mg/L, respectively, whereas xylitol production was completely inhibited at 1069 mg/L furfural, 3498 mg/L HMF and 3714 mg/L acetic acid. Furfural and acetic acid were found to be a competitive inhibitor, while uncompetitive inhibition was observed with HMF indicating negligible effect on xylitol fermentation.
Keywords: Acetic acid; furfural; HMF; Inhibition kinetics; Pichia stipitis; Xylitol fermentation